Higher expression of TNFα-induced genes in the synovium of patients with early rheumatoid arthritis correlates with disease activity, and predicts absence of response to first line therapy. Issue 1 (December 2016) - De Groof, Aurélie; Ducreux, Julie; Humby, Frances; Nzeusseu Toukap, Adrien; Badot, Valérie; Pitzalis, Costantino; Houssiau, Frédéric; Durez, Patrick; Lauwerys, Bernard
Abstract Background IL6-related T cell activation and TNFα-dependent cell proliferation are major targets of therapy in the RA synovium. We investigated whether expression of these pathways in RA synovial biopsies is associated with disease activity and response to therapy. Method Correlation and gene set enrichment studies were performed using gene expression profiles from RA synovial biopsies. Immunostaining experiments of GADD45B and PDE4D were performed on independent additional sets of early untreated RA samples, obtained in two different centers by needle-arthroscopy or US-guided biopsies. Results In 65 RA synovial biopsies, transcripts correlating with disease activity were strongly enriched in TNFα-induced genes. Out of the individual variables used in disease-activity scores, tender joint count, swollen joint count and physician's global assessment, but not CRP or patient's global assessment displayed a similar correlation with the expression of TNFα-dependent genes. In addition, TNFα-induced genes were also significantly enriched in transcripts over-expressed in synovial biopsy samples obtained from poor-responders to methotrexate or tocilizumab, prior to initiation of therapy. GADD45B (induced by TNFα in monocytes) and PDE4D (induced by TNFα in FLS) immunostaining was significantly higher in overall poor-responders to therapy in 46 independent baseline samples obtained from early untreated RA patients prior to initiation of therapy. GADD45B (but not PDE4D) immunostaining was significantly higher in the sub-group of patients with poor-response to methotrexate therapy, and this was confirmed in another population of methotrexate-treated patients. Conclusion Higher expression of TNFα-induced transcripts in early RA synovitis is associated with higher disease activity, and predicts poor response to first-line therapy. That over-expression of TNFα-induced genes predicts poor-response to therapy regardless of the drug administered, indicates that this molecular signature is associated with disease severity, rather than with specific pathways of escape to therapy.